Generating Factor Variables for Asymmetry, Non-independence and Skew-symmetry Models in Square Contingency Tables using SAS - Lawal, H. Bayo; Sundheim, Richard A. (Journal of Statistical Software, 2002)
In this paper, a SAS program (macro) is written to generate factor and regression variables required for implementing asymmetry, non-independence, non-symmetry + independence models as well as skew-symmetry models in discussed in square a x a contingency tables having nominal or ordinal categories. While several authors have developed similar factor variables for use with GLIM, we have extended this to the non-independence and the non-symmetry+independence models. The former includes both the fixed and variable distance models as well as the quasi-ordinal symmetry model. Further, our implementation of the asymmetry model in terms of the required factor variable is different from those defined for implementation of same in GLIM. Most of the models described in this paper however assume ordinal categories for the contingency table. The SAS macro developed can be applied to any square table of dimension a. We apply the models discussed in this paper to the 5 x 5 Danish mobility data that have been widely analyzed in various literatures.